Pengaruh Endorsement Terhadap Minat Membeli Produk Skin Care Halal Di Kalangan Mahasiswa Jabodetabek - Zalfa Zahirah Adhania (2021)
The increasing number of internet users in Indonesia in 2019-2020 is growing rapidly with public interest in instagram social media, which makes it a modern business marketing trend, namely endorsement. With the influence of endorsements, it makes profits for various parties, especially business people who sell their products on Instagram social media. Buying interest in halal skin care products is a very important concern for prospective Muslim consumers in consuming halal products. This study aims to examine the effect of endorsement on the interest in buying halal skin care among Jabodetabek students. This research method uses a quantitative approach with sampling through purposive sampling method which is tested on 100 active student respondents who have purchased halal skin care products. The data collection instrument used a questionnaire with a Likert scale. The analysis technique uses multiple linear regression, assisted by the SPSS 25 program. The results of the study conclude that there is a significant influence between endorsement and halal products on buying interest.